Do analysts matter for governance? Evidence from natural experiments - Chen, Jonas Tao (2015)
Building on two sources of exogenous shocks to analyst coverage (broker closures and mergers), we explore the causal effects of analyst coverage on mitigating managerial expropriation of outside shareholders. We find that as a firm experiences an exogenous decrease in analyst coverage, shareholders value internal cash holdings less, its CEO receives higher excess compensation, its management is more likely to make value-destroying acquisitions, and its managers are more likely to engage in earnings management activities. Importantly, we find that most of these effects are mainly driven by the firms with smaller initial analyst coverage and less product market competition. We further find that after exogenous brokerage exits, a CEO׳s total and excess compensation become less sensitive to firm performance in firms with low initial analyst coverage. These findings are consistent with the monitoring hypothesis, specifically that financial analysts play an important governance role in scrutinizing management behavior, and the market is pricing an increase in expected agency problems after the loss in analyst coverage.